El conscious movement in the study of guitar technique (Papeles, 2017)
Some methods for guitar propose the study of the technique through the presentation of mechanical exercises, written sequentially and that must be executed repetitively in order to achieve a motor target that allows the best potential of the hands in the performance of a musical piece. This article proposes the possibility of approaching these methods based on the conscious management of movement and on fundamental concepts related to neurological functioning and developed in studies carried out by different guitar players and neuroscience researchers.
Keywords: movement; neuroscience; guitar; technique